Content and face validity of the spanish version of the sexual self-concept inventory for early adolescent girls - Magda Liliana Villamizar Osorio; Elveny Laguado Jaimes (Universidad de Antioquia, 2019)
Objective. To determine the content and face validity of the Spanish version of the Sexual Self-Concept Inventory (O'Sullivan et al.) for early adolescent girls. Methods. Instrument-based study in which the translation, back-translation and adaptation of the 34 items of the Sexual Self-Concept Inventory (SSCI) scale was performed. Five experts carried out the content and face validation; face validation included 35 girls from the municipality of Girón (Colombia). Results. The version translated into Spanish has adequate content validity because all items exceeded the minimum CVI (0.58) value considered within an overall scale of 0.92. The face validity for the 35 early adolescent girls showed that 10 items of the instrument needed to be adjusted semantically and culturally. Conclusion. The Spanish version of the scale is semantically and conceptually equivalent to the original scale and can be used in similar contexts to evaluate sexual self-concept in early adolescent girls.    How to cite this article: Villamizar-Osorio ML, LaguadoJaimes E. Content and face validity of the Spanish version of the Sexual Self-Concept Inventory for early adolescent girls. Invest. Educ. Ill. 2019; 37(1):e02.